2004
DOI: 10.1083/jcb.200312007
|View full text |Cite
|
Sign up to set email alerts
|

Muscle satellite cells adopt divergent fates

Abstract: Growth, repair, and regeneration of adult skeletal muscle depends on the persistence of satellite cells: muscle stem cells resident beneath the basal lamina that surrounds each myofiber. However, how the satellite cell compartment is maintained is unclear. Here, we use cultured myofibers to model muscle regeneration and show that satellite cells adopt divergent fates. Quiescent satellite cells are synchronously activated to coexpress the transcription factors Pax7 and MyoD. Most then proliferate, down-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
850
1
21

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 817 publications
(916 citation statements)
references
References 65 publications
(102 reference statements)
44
850
1
21
Order By: Relevance
“…We found that increased expression of Pax7 protein coincided with the increased number of SCs in mesterolone-treated chickens when compared to control chickens. Zammit et al (2004) reported that activated SCs maintain high levels of Pax7. The increase in Pax7 protein expression in mesterolone-treated birds is most probably due to enhanced activation and proliferation of SCs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that increased expression of Pax7 protein coincided with the increased number of SCs in mesterolone-treated chickens when compared to control chickens. Zammit et al (2004) reported that activated SCs maintain high levels of Pax7. The increase in Pax7 protein expression in mesterolone-treated birds is most probably due to enhanced activation and proliferation of SCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies have pointed to a role for Pax genes in the maintenance of progenitor cells. For example, Pax7 is expressed in skeletal muscle satellite cells, a resident progenitor population that can generate new myoblasts (Seale et al, 2000;Zammit et al, 2004). In Pax7 mutants, satellite muscle cells are formed, but in reduced numbers that fall further over time (Zammit et al, 2004).…”
Section: Control Of Cell Division By Pax2mentioning
confidence: 99%
“…For example, Pax7 is expressed in skeletal muscle satellite cells, a resident progenitor population that can generate new myoblasts (Seale et al, 2000;Zammit et al, 2004). In Pax7 mutants, satellite muscle cells are formed, but in reduced numbers that fall further over time (Zammit et al, 2004). In addition, forced expression of Pax7 in satellite cells prevents their difference into myoblasts (Olguin and Olwin, 2004).…”
Section: Control Of Cell Division By Pax2mentioning
confidence: 99%
“…Des études ex vivo faites sur des fibres isolées qui étaient en phase de prolifération ont montré qu'un petit nombre des cellules précurseurs myogéniques (mpc) issues de la division des cellules satellites ne s'engagent pas dans la différenciation terminale mais constituent une réserve des cellules progénitrices sans qu'on puisse, dans ces conditions expérimen-tales de manipulation de fibres isolées, les nommer cellules satellites [5]. En culture, on observe également cette propriété d'autorenouvellement, puisqu'une sous-population des mpc constitue les « cellules de réserve » (RC) : ces cellules qui ne sont pas engagées dans le cycle cellulaire et sont indifférenciées peuvent donner naissance à des cellules différenciées et à de nouvelles RC dès lors qu'elles sont réensemencées et activées ; elles expriment plusieurs des caractéristiques des cellules satellites 1 [5]. En conséquence, les cellules satellites, ou une sous-population d'entre elles, sont considérées comme les cellules souches du muscle [3,6,7].…”
Section: Nouvelleunclassified
“…La puissance de cette démarche s'appuie sur la qualité des bases de données des polymorphismes humains comme la dbSNP, la plus prometteuse étant celle en cours d'élaboration par le « 1 000 genomes project » [5]. Sachant que sur les 6 000 maladies génétiques connues seuls 1 600 gènes responsables ont été identifiés, l'émergence de ces nouvelles technologies est porteuse d'un réel espoir pour plus de 75 % des patients atteints de maladies génétiques chez lesquels aucun diagnostic génétique n'est possible à ce jour.…”
unclassified